2015
DOI: 10.1007/s00125-015-3568-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 4 inhibits insulin secretion from rodent beta cells through regulation of calbindin1 expression and reduced voltage-dependent calcium currents

Abstract: Aims/hypothesis Type 2 diabetes is characterised by progressive loss of pancreatic beta cell mass and function. Therefore, it is of therapeutic interest to identify factors with the potential to improve beta cell proliferation and insulin secretion. Bone morphogenetic protein 4 (BMP4) expression is increased in diabetic animals and BMP4 reduces glucose-stimulated insulin secretion (GSIS). Here, we investigate the molecular mechanism behind this inhibition. Methods BMP4-mediated inhibition of GSIS was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The impaired Ca 2 + response and particularly the reduced re-uptake of Ca 2 + to ER in rosuvastatin treated mice prompted us to investigate the expression of ER-related genes; SERCA2 , SERCA3 , Sel1l and CHOP (Chen et al, 2014, Francisco et al, 2011, Ravier et al, 2011) together with Calb1 , a gene we previously suggested to be involved in Ca 2 + buffering (Christensen et al, 2015). Rosuvastatin reduced the expression of CHOP in mice on ND, but had no effect on the expression of the other genes investigated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The impaired Ca 2 + response and particularly the reduced re-uptake of Ca 2 + to ER in rosuvastatin treated mice prompted us to investigate the expression of ER-related genes; SERCA2 , SERCA3 , Sel1l and CHOP (Chen et al, 2014, Francisco et al, 2011, Ravier et al, 2011) together with Calb1 , a gene we previously suggested to be involved in Ca 2 + buffering (Christensen et al, 2015). Rosuvastatin reduced the expression of CHOP in mice on ND, but had no effect on the expression of the other genes investigated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of DM2 as a covariate, the GWAS identified several additional SNPs on chromosome 8, as well as SNPs on chromosomes 17 and 19. These additional SNPs were previously linked to BMI and obesity in other studies (Christensen et al 2015;Nakajima et al 2016;Thomsen et al 2016). Manhattan plots for the two BMI GWAS studies are presented in Figure 1 and Supplementary Figure S2, with the linear associations results presented in Table 3.…”
Section: Gwas Of Bmi In the Healthy Nevada Cohortmentioning
confidence: 93%
“…Fura 2-AM (4 μmol/l) (TEFLabs, Austin, TX, USA) were applied for 40 min followed by 30 min of de-esterification in imaging buffer. Imaging was performed as previously described [31]. One frame per second was recorded at 37°C under perfusion at 0.7 ml/min for 5 min at 2.8 mmol/l glucose, followed by 20 min at 16.7 mmol/l glucose, then 20 min at 2.8 mmol/l glucose with or without AMS.…”
Section: Methodsmentioning
confidence: 99%